2018
DOI: 10.5603/gp.a2018.0015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of the Quadratus Lumborum Block type I using ropivacaine in postoperative analgesia after a cesarean section — a controlled clinical study

Abstract: Objectives: Quadratus Lumborum Block in contrast to Transversus Abdominis Plane Block contains a unique component which not only stops somatic pain but also inhibits visceral pain by spreading the local anesthetic to the paravertebral space. This study was designed to determine whether performing the Quadratus Lumborum Block type I in patients undergoing cesarean section would be associated with both decreased morphine consumption and decreased pain levels in the postoperative 48-hour period. Material and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 30 publications
5
72
1
3
Order By: Relevance
“…The proportion of patients with opioid sparing effects in our study suggests that the analgesic effect of QLB can last 6 to 10 hours, but not 24 or 48 hours as previously reported. 20 This result is similar to the ndings of Mieszkowski MM, et al 21 , Krohg A, et al 22 and Tamura T, et al 13,17 , all of whom found the bene t of QLB to be less than 24 hours. In 2018, Mieszkowski MM, et al reported the time from C-section until the rst dose of morphine to be approximately 10 hours in the QLB1 group.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The proportion of patients with opioid sparing effects in our study suggests that the analgesic effect of QLB can last 6 to 10 hours, but not 24 or 48 hours as previously reported. 20 This result is similar to the ndings of Mieszkowski MM, et al 21 , Krohg A, et al 22 and Tamura T, et al 13,17 , all of whom found the bene t of QLB to be less than 24 hours. In 2018, Mieszkowski MM, et al reported the time from C-section until the rst dose of morphine to be approximately 10 hours in the QLB1 group.…”
Section: Discussionsupporting
confidence: 87%
“…The cumulative morphine use (mg) and demands between groups are shown in Table 6. The proportion of patients without morphine requirement at 6, 8, 10, and 12 hours postoperatively in Group IT morphine vs. Group IT morphine with QLB was 10 (37%) vs. 21 No patients in Group QLB experienced pruritus compared with other two groups (55% in Group IT morphine and 16.7% in Group IT morphine with QLB) at the 2 nd interim analysis (Table 1). However, the number of parturients who experienced postoperative nausea and vomiting was comparable among the study groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute pain after CS has both somatic and visceral components that result from surgical cutting of the abdominal wall and uterus. TAP block, as a part of a multimodal analgesic regimen after CS, provides effective analgesia for somatic pain at the abdominal wall [9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the QLB technique was modified by shifting the injection point from the anterolateral border of the quadratus lumborum to the posterior border (QLB II) [10]. QLB inhibits the dual pain components (somatic and visceral) as a result of local anesthetic spreading to the paravertebral space [9,10]. The analgesic efficacy of QLB II and its superiority over TAP block after CS were proved by Blanco [10,11].…”
Section: Introductionmentioning
confidence: 99%